The Incorporation of Chromium in Rice Straw Fermented with Ganoderma lucidum - F Agustin; T Toharmat; D Evvyernie; D Taniwiryono; S Tarigan (Faculty of Animal Science, Bogor Agricultural University, 2013)
The research was designed to evaluate chromium incorporation by Ganoderma lucidum in rice straw substrate supplemented with chromium chloride. Treatments were combination of Cr level (0, 500, 1000, 1500, 2000, 25000, and 3000 ppm) and fermentation time (0, 2, 3, and 4 wk). The treatments were arranged in a factorial 7 x 4 and allocated in completely randomized design with three replications. G. lucidum was grown in potato dextrose agar (PDA) medium for 10 days and was inoculated to the substrate which have been sterilized and mixed with CrCl3.6H2O. The moisture of substrate was maintained at 70%. Fiber and protein components of growth media of G. lucidum was determined and analyzed for their Cr content. The finding result showed that addition of Cr up to 3000 ppm into the substrate stimulated the G. lucidum growth. Chromium was incorporated into the fiber and protein components of the growth substrate of G. lucidum during fermentation. Incorporation of Cr into the protein of substrate containing3000 ppm Cr was highest when fermented for 4 wk. Protein component of substrate contained 9.29% Cr while in NDF and ADF was 27.20% and 10.55% Cr, respectively. It is concluded that Cr was incorporated into the G. lucidum cells during fermentation.